In Service of Emergent India : A Call to Honor - Singh, Jaswant, 1938-2020 (Book collections on Project MUSE., 2007)
In Service of Emergent India is an evocative insider's account of a crucial period in India's history. It provides an in-depth look at events that changed the way the world perceived India, and a unique view of Indian statecraft. As Minister of External Affairs, Defense, and Finance in the BJP-led governments of 1996 and 1998-2004, Jaswant Singh was the main foreign policy spokesman for the government of Atal Bihari Vajpayee during the 1998 nuclear tests by India and Pakistan, the hijacking to Kandahar, Afghanistan, of Indian Airlines flight IC 814, and the Kargil conflict between India and Pakistan, as well as other key events. In an account that is part memoir, part analysis of India's past and future prospects, Singh reflects on his childhood in rural Rajasthan at the end of the colonial period, his schooling and military training, and memories of Indian Independence and the Partition of India and Pakistan. He analyzes the first four decades of Indian nationhood under Congress Party rule, ongoing tensions between India and Pakistan, Sino-Indian relations, and post-9/11 U.S.-Indian relations.